Philosophy of Science and Political Philosophy, the Methodological Effect of Modern Science on the Political Law - morteza mahdiha (حکمت و فلسفه, 2009)
In the middle of sixteenth century, publishing of Copernicus' On the Revolutions of the Celestial Spheres led to the Copernican scientific revolution. This movement continued by publishing of Kepler's and Galileo's works in the early of seventeenth century. According to the common construal, in this methodological revolution, deduction is replaced by induction. In traditional science, a few universal propositions possessed the main value and a vast collection of particular propositions were derived from them. This path in conversed in modern science and few general laws acquire their validity from sets of particular propositions. In other words, particular experimental propositions have essential validity and general laws gain their value in a derived way. After this methodological revolution in science, important transitions occurred in the political philosophy. The thesis of this paper is that these transitions are affected by the mentioned changes in the philosophy if science.